Bioactive Components of Chinese Propolis Water Extract on Antitumor Activity and Quality Control. (30th March 2016) - Xuan, Hongzhuan; Wang, Yuehua; Li, Aifeng; Fu, Chongluo; Wang, Yuanjun; Peng, Wenjun
Abstract : To understand the material basis of antitumor activity of Chinese propolis water extract (CPWE), we developed a simple and efficient method using macroporous absorptive resin coupled with preparative high performance liquid chromatography and separated and purified eleven chemical components (caffeic acid, ferulic acid, isoferulic acid, 3, 4-dimethoxycinnamic acid, pinobanksin, caffeic acid benzyl ester, caffeic acid phenethyl ester, apigenin, pinocembrin, chrysin, and galangin) from CPWE; then we tested the antitumor activities of these eleven components using different human tumor cell lines (MCF-7, MDA-MB-231, HeLa, and A549). Furthermore, cell migration, procaspase 3 level, and reactive oxygen species (ROS) of effective components from CPWE were investigated. Our data showed that antitumor activities of the eleven components from CPWE were different from each other. CPWE and its effective components induced apoptosis by inhibiting tumor cell migration, activating caspase 3, and promoting ROS production. It can be deduced that the antitumor effects of propolis did not depend on a single component, and there must exist "bioactive components, " which also provides a new idea for Chinese propolis quality control.